1991
DOI: 10.1073/pnas.88.18.8116
|View full text |Cite
|
Sign up to set email alerts
|

Histidine pKa shifts accompanying the inactivating Asp121----Asn substitution in a semisynthetic bovine pancreatic ribonuclease.

Abstract: A senisynthetic RNase, RNase-(1-118)-(111-124), consising of a noncovalent complex between residues 1-118 of RNase (obtained from the proteolytic digestion of RNase A), and a synthetic 14-residue peptide containing residues 111-124 of RNase, exhibits 98% of the enzymatic activity of bovine pancreatic ribonuclease A (EC 3.1.27.5). The replacement of aspartic acid-121 by asparagine in this semisynthetic RNase to form the "D121N" analog reduces kd,/K. to 2.7% of the value for RNase A. In the present work, lH NMR … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
23
1

Year Published

1997
1997
2012
2012

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(28 citation statements)
references
References 34 publications
4
23
1
Order By: Relevance
“…The positively charged residue (Arg and Lys) may decrease the pK a value of His, while the negatively charged residue (Asp and Glu) reverses the effect. [33][34][35] In addition, the hydrophobic environment is proposed to reduce the pK a values of His. 36,37 Our results showed that several positively charged surface residues are clustered near the catalytic histidine residues His10 and His97, while negatively charged residues are 12 Å away from them ( Figure 5(c)).…”
Section: Discussionmentioning
confidence: 99%
“…The positively charged residue (Arg and Lys) may decrease the pK a value of His, while the negatively charged residue (Asp and Glu) reverses the effect. [33][34][35] In addition, the hydrophobic environment is proposed to reduce the pK a values of His. 36,37 Our results showed that several positively charged surface residues are clustered near the catalytic histidine residues His10 and His97, while negatively charged residues are 12 Å away from them ( Figure 5(c)).…”
Section: Discussionmentioning
confidence: 99%
“…If this interaction occurs when sTnI(115-131) is bound to cNTnC, then it will also contribute to an increase in the pK a of His-130. Glu-16 is also near His-130 (10.1 Å), and it may be involved in driving sTnI binding to sTnC, because electrostatic forces can span distances Ͼ10 Å (55)(56)(57)(58)(59). Conversely, in the NMR and x-ray structures of cardiac troponin, these interactions do not occur, presumably because the histidine is replaced by an alanine (19,20).…”
Section: Discussionmentioning
confidence: 99%
“…The semisynthetic D121N analog has 5% of the catalytic activity of the analogous wild-type semisynthetic enzyme. A difficulty with interpreting the results of this study, however, is that the three-dimensional structure of the semisynthetic D121N analog exhibits numerous changes compared to that of the analogous wild-type semisynthetic enzyme (29,30). In another study, site-directed mutagenesis was used to replace Asp121 in RNase A itself with a glutamate residue (31).…”
Section: Nih-pa Author Manuscriptmentioning
confidence: 99%